2000
DOI: 10.1038/sj.leu.2401880
|View full text |Cite
|
Sign up to set email alerts
|

A novel RT-PCR-based protein activity truncation assay for direct assessment of deoxycytidine kinase in small numbers of purified leukemic cells

Abstract: In vitro studies have demonstrated that deoxycytidine kinase (dCK) plays a crucial role in the mechanism of resistance to cytarabine (AraC). The resistant phenotype in vitro is always a result of mutational inactivation of dCK, leading to defects in the metabolic pathways of AraC. Although inactivation of dCK has shown to be one of the major mechanism of resistance to AraC in vitro, limited in vivo data are available. To improve research concerning the involvement of dCK inactivation in patients with acute mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Error bars indicate SDs. tween mutational inactivation of dCK and resistance of nucleoside analogues, [20][21][22][23] so we sequenced dCK mRNA. Most of the coding regions of dCK were amplified and sequenced directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Error bars indicate SDs. tween mutational inactivation of dCK and resistance of nucleoside analogues, [20][21][22][23] so we sequenced dCK mRNA. Most of the coding regions of dCK were amplified and sequenced directly.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we did not detect any mutation in dCK mRNA in the lung cancer cell lines or the gemcitabine-resistant sublines (data not shown), even though previous studies showed that resistance to nucleotide analogues was mediated by mutation in dCK. [20][21][22][23] In this connection, it is noteworthy that mutational inactivation of dCK in patients with refractory or relapsed acute myeloid leukemia is rarely observed. 33,34) Though the mechanisms of dCK inhibition remain to be fully elucidated, we consider that decreased gemcitabine metabolism to its active form by dCK inactivation is one of the mechanisms of development of acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
“…An AraC-resistant cell line was derived after limiting dilution of an ex vivo-generated AraC-resistant leukemic cell line, designated K7 in this article. 24 In this cell line AraC resistance was caused by the deletion of dCK.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 97%
“…24 Briefly, total cellular RNA was isolated from 10 6 cells by using TRIzol (Gibco BRL, Life Technologies, Gaithersburg, MD) according to the manufacturer's protocol. Two micrograms total RNA was reverse transcribed into single-strand cDNA.…”
Section: Dck Reverse Transcription-polymerase Chain Reactionmentioning
confidence: 99%
“…Recently, Veuger et al 7 described AML patients in whom the resistant phenotype was not associated with dCK mutations, but with the expression of alternative splice variants in addition to the wild-type dCK. The alternatively spliced transcripts, in which one or more exons were deleted, were shown to code for enzymic inactive proteins in vitro.…”
mentioning
confidence: 99%